Assessing Globalization Competences in the Information Systems Domain – Instruments and Methods - Stén, Tiia (2012)
Stén, Tiia Assessing Globalization Competences in the Information Systems Domain – Instruments and Methods Jyväskylä: University of Jyväskylä, 2012, 36 p. Information Systems Science, Bachelor’s thesis Supervisor: Pawlowski, Jan The goal of this bachelor’s thesis is to research suitable competence assessment instruments and methods for assessing globalization competence in the Infor-mation Systems domain. Within the framework of the study, globalization competences are the skills and abilities required from an individual in order for him or her to perform effectively in an international context in the Information Systems field. The results of the analysis indicate that the most applicable competence assessment methods for assessing globalization competences in the Information Systems domain are written format assessments (especially essays), candidate self-reports, live interactions (especially group work) and computer simulations. The primary method of the research was literature analysis which was conducted on the concept of globalization competences and competence as-sessment models. Thereafter a design-science research approach was taken in order to address the research problem and match the globalization competences with suitable competence assessment methods. Finally, the validity of the outcome was confirmed through an appraisal of the practical applicability of the suggested competence assessment methods in relation to the learning objectives of two university courses of different com-plexity levels.